Phosphate ester side‐chain‐modified conjugated polymer for hybrid solar cells. Issue 26 (3rd March 2017) - Zhang, Zhongqiang; Jin, Zhengneng; Fu, Weifei; Shi, Minmin; Chen, Hongzheng
ABSTRACT: Although nanocrystals have several advantages of tunable bandgap and high carrier mobility, it is still challenging to achieve high‐performance polymer: nanocrystals hybrid solar cells (HSC) due to the complicated surface problem. Many efforts have been devoted to replace the long alkyl chain on the surface of nanocrystals to improve the charge transfer and transport. Herein, we modified the alkyl chain in poly[2, 6–(4, 4‐ bis (2‐ethylhexyl)−4H‐cyclopenta[2, 1‐b;3, 4‐b′]‐dithiophene)‐ alt ‐4, 7–(2, 1, 3‐benzothiadiazole)] (PCPDTBT) by phosphate ester. Due to its strong affinity to CdSe nanocrystals, the resulting polymers can spontaneously exchange the long chain ligands in one‐step process. With the improved morphology of polymer: CdSe blended film, a power conversion efficiency (PCE) of 3.12% was achieved for hybrid solar cells. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45003. Abstract :